2011
DOI: 10.1002/anie.201006587
|View full text |Cite
|
Sign up to set email alerts
|

Tuning a P450 Enzyme for Methane Oxidation

Abstract: A new spin: The addition of chemically inert perfluoro carboxylic acids (green; see picture) to P450 enzymes results in dramatic activation of their catalytic activity as a result of the conversion of the Fe/heme from a low‐spin to a high‐spin state, and the reduction of the binding‐pocket size. Together these effects allow otherwise inert substrates such as propane and even methane to be oxidized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(107 citation statements)
references
References 82 publications
3
101
0
3
Order By: Relevance
“…In CYP102, the presence of perfluorinated fatty acids greatly improved the ability of the enzyme to hydroxylate the gaseous hydrocarbons, such as butane, propane, ethane, and even methane [50, 106]. Similar approach termed ‘decoy substrate’ was successfully used in peroxygenase CYP152A1 to significantly improve the efficiency of catalytic oxidation of styrene and ethylbenzene by addition of the short-chain fatty acids [107-108].…”
Section: Heterotropic Cooperativitymentioning
confidence: 99%
“…In CYP102, the presence of perfluorinated fatty acids greatly improved the ability of the enzyme to hydroxylate the gaseous hydrocarbons, such as butane, propane, ethane, and even methane [50, 106]. Similar approach termed ‘decoy substrate’ was successfully used in peroxygenase CYP152A1 to significantly improve the efficiency of catalytic oxidation of styrene and ethylbenzene by addition of the short-chain fatty acids [107-108].…”
Section: Heterotropic Cooperativitymentioning
confidence: 99%
“…1b, left), our research group and Zilly et al recently reported that even wildtype P450BM3 can catalyze the hydroxylation of small alkanes in the presence of a series of perfluorocarboxylic acids (PFs) with alkyl chain lengths from 5 to ; the latter perfluorinated compounds were named "decoy molecules" (Fig. 1b, right) [12,13]. According to the reaction mechanism of fatty acid hydroxylation by P450BM3 (Fig.…”
Section: Introductionmentioning
confidence: 89%
“…30,31 While the conversion of propane to propanol in the presence of PFC10 proceeded successfully, 30 the original conclusion that methane was oxidized to methanol was later refuted. 35 In the presence of decanoic acid P450 BM3 did not convert propane to propanol, suggesting that the fluorine atoms in the decoy molecule are crucial for coercing the enzyme to accept small alkane substrates. 31 More recently, Watanabe, Shoji and colleagues reported successful hydroxylation of aromatic rings such as those of benzene, toluene, anisole, chlorobenzene, nitrobenzene and acetophenone using P450 BM3 and various PFCs (Table 3).…”
Section: Effect Of Perfluorinated Fatty Acid Decoy Molecules On P450 mentioning
confidence: 99%